THERMO-MAGNETO-ELASTIC ANALYSIS IN A CURRENT-CARRYING SHELL WITH CLAMPED PERIMETERS - BIAN YuHong; ZHANG Chen (Jixie qiangdu)
A thermo-magneto-elastic problem for a current-carrying shell with clamped perimeters in a magnetic field was studied. Based on the kinetic equations, geometric equations, physical equations, and electrodynamics equations, the fundamental equations of a current-carrying shell under the interaction of a mechanical field,an electromagnetic field,and a temperature field were given. The nonlinear partial differential equations including 10 basic unknown variables were established.Using Newmark’s stable finite equidifferent formulas,normal type which can be solved by the discrete-orthogonalization method was obtained. For the shell with clamped perimeters,the expressions for the Lorentz force,the temperature field,and the integral eigenvalues of the temperature field were derived. The change rules of stresses,temperatures,and deformations in the currentcarrying shell with the electromagnetic parameters were analyzed. It is proved that the stresses,strains,and temperatures in plates and shells can be controlled by changing the electromagnetic and mechanical parameters through the example calculation. This provides a method of theoretical analysis and numerical calculation for changing the service conditions and intensity researches of plate and shell structures in an electromagnetic field.